Optical Stiffness of an Optically Trapped 4-Cyano-4’-Pentylbiphenyl (5CB) in the form of a Microdroplet in Water - Yeng, Muhamad Safuan Mat; Ayop, Shahrul Kadri; Mustapa, Izan Roshawaty; Sasaki, Keiji (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aimed to determine the optical stiffness (